Corrosion resistance of X12CrMoWVNbN10-1-1 steel in NaCl solutions at different pH values - Pejić Jovanka; Kosec Borut; Pantić Olga; Volkov-Husović Tatjana; Zorc Matija; Vlahović Milica (Podzemni Radovi, 2025)
The influence of pH on the corrosion behavior of X12CrMoWVNbN10-1-1 steel was examined in 0.1 M NaCl solution. The rate of general (uniform) corrosion of the tested steel was determined using linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS) methods. In the NaCl solution with a pH of 2.9, the tested steel exhibited a more negative corrosion potential and lower corrosion resistance. Significantly higher corrosion potential and resistance to general corrosion were observed in a neutral solution (pH = 6.5), where the steel was in a passive state.